The Fate of Dividing Cells During Lens Morphogenesis, Differentiation and Growth - Kallifatidis, Georgios (2011)
Early in development, the ocular lens establishes its distinctive architecture, and this is maintained throughout life as the lens continues to grow. This growth is tightly regulated through the proliferation of the lens epithelial cells and their subsequent differentiation into specialised elongated fiber cells. Although much work has been carried out to define these patterns of growth, very little has been reported on the detailed fate and kinetics of lens cells during embryogenesis. Using BrdU-incorporation, the present study has attempted to follow the fate of lens cells that have undergone at least one round of DNA synthesis during the early stages of lens morphogenesis. Results from this work have confirmed that the rate of lens cell proliferation and new fiber cell differentiation progressively slows as the lens differentiates and grows. In addition, these studies have shown that early in lens development, not all DNA synthesis is restricted to the lens epithelium, with some elongating fiber cells retaining the ability to undergo DNA synthesis. Adopting this system we have also been able to place the initiation of secondary fiber cell differentiation in the mouse lens by E12.5, concomitant with the loss of the lens vesicle lumen by the elongating primary fiber cells. Overall, this study has allowed us to revisit some of the mechanisms involved in early lens development, has provided us with insights into the fate of cells during this rapid phase of murine lens growth, and has provided a novel method to study the rate of new fiber cell differentiation over a defined period of lens development and growth.